(untitled) (Research, Society and Development, 2021)
In this work, an excerpt from a master’s thesis, the creation of an educational RPG (Role Playing Game) game is presented, which can be used in classroom or remote teaching, in a fixed or evaluative way. This playful study addresses the theme of Bohr’s atomic model, spectral lines and quantum numbers, at the high school level, represented within a stellar adventure. The development of the game is associated with D & D games, however, we report from now on that they are RPGs that can be created in different scenarios, addressing multiple contents and narratives, depending on the way the teacher wishes to handle it in the classroom. class.